Use of Acidic Hydrolysis and Diazo Coupling Reaction for Spectrophotometric Determination of Furosemide in Urine and Pharmaceutical Formulation. - Ali, Hawraa; muhammed, Sumayha (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Simple and rapid spectrophotometric determination of furosemide (FUR) has been investigated .The method is based on acid hydrolysis of FUR to free primary aromatic amine and diazotization followed by coupling with 3, 5 di methyl phenol (3, 5-DMPH) at basic medium. The absorbance was measured at 434 nm, the method was optimized for best condition, and beers’ law is obeyed over the range of 0.4-50 µg.mL-1 with molar absorptivity and sandal’s sensitivity 1.3899 x104 L moL-1 .cm-1 and 0.0238x104 µg.cm-2 respectively. Analysis of solution containing nineteen different concentrations of FUR gave a correlation coefficient of (0.9999) and limit of detection, limit of quantitation were 0.127, 0.464µg.mL-1 respectively. The reaction stoichiometry was evaluated by Job’s and mole ratio method was found to be 1:1(diazotized FUR: 3, 5-DMPH) .The method was applied in synthetic urine and pharmaceutical formulation. The recovery of FUR in spiked urine was satisfactory resulting in the values of (99±3.32) %, the results of the suggested method was compared with available official literature method.